Morphological and genetic identification and isotopic study of the hair of a cave lion (Panthera spelaea Goldfuss, 1810) from the Malyi Anyui River (Chukotka, Russia). (15th June 2016) - Chernova, O.F.; Kirillova, I.V.; Shapiro, B.; Shidlovskiy, F.K.; Soares, A.E.R.; Levchenko, V.A.; Bertuch, F.
Abstract: We present the first detailed analyses of the preserved hair of a cave lion ( Panthera spelaea Goldfuss, 1810). The hair was found in association with a skeleton that was recovered recently from perennially frozen Pleistocene sediments in the lower reaches of the Malyi Anyui River (Chukotka, Russia). We extract mitochondrial DNA from the hair to confirm its taxonomic identity, and perform detailed morphological analyses of the color and structure of the hair using light optical microscopy and SEM. In addition, we compare the cave lion hair to hair taken from the back and mane of an African lion. We find that cave lion hair is similar but not identical to that of the present-day lion. In addition to slightly different coloration, cave lions had a very thick and dense undercoat comprising closed and compressed wavy downy hair with a medulla. In addition, while the microstructures of the medulla and cortex of cave lion hair are similar in extinct and living lions, the cuticular scales of cave lion hair are higher than those in living lions, suggesting that cave lion hair is stronger and more robust than that of living lions. We hypothesize that the differences between cave lion hair and present-day lion hair may be due to adaptations of cave lions to the harsh climatic and environmental conditions of the Pleistocene Ice Ages. Graphical abstract: Highlights: First morphological analyses of a cave lion hair found in Chukotka are presented. Its undercoat composed of numerous downy hairs was an adaptation to the Ice Age. Cave lion hair was similar but not identical to those of the present-day lions.